Recycled carbon fiber nonwoven functionalized with fluorine-free superhydrophobic PDMS/ZIF-8 coating for efficient oil-water separation. Issue 6 (December 2021) - Pakdel, Esfandiar; Wang, Jinfeng; Varley, Russell; Wang, Xungai
Abstract: This study introduces a feasible approach for producing a functional nonwoven from carbon fiber waste and demonstrates its excellent performance in oil-water separation. Carbon fiber scraps were recycled into a nonwoven product through conventional textile processing methods of carding and needle-punching, followed by surface modification with fluorine-free coatings containing polydimethylsiloxane (PDMS) and zeolite imidazole framework-8 (ZIF-8) particles. The capacity of PDMS/ZIF-8 coating to impart superhydrophobic-superoleophilic properties to the developed nonwoven was investigated, particularly for organic solvents/oils absorption, and oil-water separation. Different characterization techniques including scanning electron microscopy (SEM), X-ray diffraction (XRD), BET surface area, X-ray photoelectron spectroscopy (XPS), and thermogravimetric analysis (TGA) were used to characterize the synthesized ZIF-8 particles and developed coatings. The results showed that the application of PDMS initially increased the water contact angle, but its excess amount lowered the superhydrophobicity and absorption capacity of coated nonwovens. The presence of ZIF-8 particles boosted the superhydrophobicity and absorption capacity where the sample coated with PDMS/ZIF-8 exhibited superior superhydrophobicity having a water contact angle of 153.5°. The PDMS/ZIF-8 coated nonwoven displayed a highly efficient gravity-driven and continuous oil-water separation performance. This research presents a sustainable approach to the development of a multifunctional carbon fiber nonwoven with excellent oil-water separation capability from waste materials. Graphical Abstract: ga1 Highlights: A feasible sustainable approach was developed to fabricate value-added nonwovens from carbon fiber waste. Fluorine-free coating of PDMS/ZIF-8 was developed on recycled carbon fiber nonwoven. Water contact angle of 153.5° was achieved and the roles of PDMS and ZIF-8 were clarified. Excellent oil-water separation efficiency of >99% was achieved even up to 15 cycles. Superhydrophobicity and oil-water separation performance were maintained in acidic and alkali conditions.